The Medical Follow-up Agency: The First Fifty Years, 1946-1996 - Medicine, Institute of; Santangelo, Mark J; Berkowitz, Edward D (The Compass series, 2000)
The Medical Follow-up Agency is a national treasure for veterans and for long-term studies of health. Its data resources provide incomparable opportunities to follow very important populations and to ask creative questions about their well-being as well as the occurrence and significance of illness. The Twin Registry provides an opportunity to understand the impact of heredity on health and disease in a population of more than 16,000 pairs of twins (i.e., 32,000 veterans). The Medical Follow-up Agency is a living tribute to the vision, energy, and effectiveness of Michael E. DeBakey, M.D. Dr. DeBakey created the idea for the agency, obtained the appropriate approvals, staffed its initial creation, and 50 years later, spoke on the occasion of its golden anniversary. This sequence of events must be unique in the history of veterans' health and medical research.